PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMILIHAN MEREK SEPEDA MOTOR - Tantri Ryanthi; Budi Suharjo; Istiqlaliyah Muflikhati (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2016)
This study was conducted to identify factors that affect the promotion of the consumers in making the decision to choose the motorcycle brand and to measure how large the contribution is to the promotion of consumer purchasing decisions. This study used Thurstone, correspondence analysis and Structural Equation Model (SEM) analysis method to obtain the expected results. About 106 respondents representing consumers were interviewed directly by using a structured questionnaire. The results showed that consumers are more interested in the factors associated with the products, prices and after sales service in choosing a brand of motorcycles. Based on the results of the study, contributions to promotion among other 7P marketing mix provide the most minor influence on the purchase decision of motorcycle. To find out how to examine the decision-making process, this study used the theory of decision-making process as the basis of research framework that stated consumers go through several stages in the decision-making process which consists of needs recognition, information finding, evaluation of alternatives, and eventually the act of purchase. Keywords: promotion, motorcycle, correspondence, Thurstone, SEM, recommendation